Texas Senate Bill 8 significantly reduced travel to abortion clinics in Texas - Andersen, Martin S.; Marsicano, Christopher; Pineda Torres, Mayra; Slusky, David (Frontiers in Global Women's Health, 2023)
The Dobbs v. Jackson decision by the United States Supreme Court has rescinded the constitutional guarantee of abortion across the United States. As a result, at least 13 states have banned abortion access with unknown effects. Using 'Texas' SB8 law that similarly restricted abortions in Texas, we provide insight into how individuals respond to these restrictions using aggregated and anonymized human mobility data. We find that 'Texas' SB 8 law reduced mobility near abortion clinics in Texas by people who live in Texas and those who live outside the state. We also find that mobility from Texas to abortion clinics in other states increased, with notable increases in Missouri and Arkansas, two states that subsequently enacted post-Dobbs bans. These results highlight the importance of out-of-state abortion services for women living in highly restrictive states.